Verletzungsmuster und Prävention im Weltcup-Windsurfing - Gosheger, G.; Jagersberg, K.; Linnenbecker, S.; Meissner, H. J.; Winkelmann, W. (Sportverletzung Sportschaden, 2001)
The aim of the present study was to analyze the injury patterns in professional world cup windsurfing. The one handed jumps and loops are combined with a high risk of injury. 49 world cup professional windsurfers (39 men, 10 women) could be asked regarding their injuries in their professional career. Questionnaires were used in German, English or French. Furthermore the windsurfers were asked about prophylaxis against injuries. 260 injuries could be stated: 43 injuries of the head (17%), 40 injuries of the trunk (15%), 23 injuries of the upper extremity (9%). The majority of the injuries were stated at the lower extremity (n = 154, 59%). As far as the lower extremity is concerned, the strain of the ankle joint was dominating (n = 57). With 22% of all mentioned injuries this was the most common injury and 61% of the windsurfers claimed about an injury of the ankle joint. An injury of the knee was stated in 30 windsurfers, whereby 80% of these injuries were severe injuries of the ligaments or the meniscus. Only 10% of the professionals used a helmet to prevent injuries of the head. The cause of the head injuries are the spectacular jumps like loopings or table tops. The cumulation of injuries of the lower extremity is due to the fixation of the feet in the footstraps. The fixation on the feet leads to extreme rotatory forces in the knee joint in case of a fall. Furthermore the fixation of the feet leads to a high rate of ankle joint strain. In order to prevent injuries a helmet should be used and special footstraps should be developed, which ensure a release of the foot in the danger area.